2014
DOI: 10.4269/ajtmh.13-0164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Emerging Q Fever in French Guiana and Endemic Q fever in Marseille, France

Abstract: Abstract. Q fever is an emergent disease in French Guiana. We compared the incidence clinical and serologic profiles between patients from Cayenne, French Guiana and Marseille in metropolitan France during a four-year period. The annual incidence of diagnosed acute Q fever was significantly higher in Cayenne (17.5/100,000) than in Marseille (1.9/100,000) (P = 0.0004), but not the annual incidence of endocarditis (1.29 versus 0.34/100,000). Most patients had fever (97%) and pneumonia (83%) in Cayenne versus 81%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 25 publications
4
37
1
1
Order By: Relevance
“…Therefore, there is a real outbreak in Cayenne linked to a unique and exclusive clone, which likely explains the distinct clinical manifestation observed with the Cayenne "geotype". 12 Recently in a collaborative work done with Bernard Davoust, we were able, after a hundred samples tested from animals, to identify the three-toed sloth (Fig. 1) as the likely source of the Q Fever outbreak in Cayenne in French Guiana.…”
Section: The Outbreak In Guyanamentioning
confidence: 97%
“…Therefore, there is a real outbreak in Cayenne linked to a unique and exclusive clone, which likely explains the distinct clinical manifestation observed with the Cayenne "geotype". 12 Recently in a collaborative work done with Bernard Davoust, we were able, after a hundred samples tested from animals, to identify the three-toed sloth (Fig. 1) as the likely source of the Q Fever outbreak in Cayenne in French Guiana.…”
Section: The Outbreak In Guyanamentioning
confidence: 97%
“…Whole lungs and whole spleens were homogenized in PBS, and DNA from lung suspensions (200 l), spleen suspensions (100 l), and blood (200 l) was extracted using a QIAamp tissue kit (Qiagen) in a 100-l final volume. Quantitative real-time PCR (qPCR) was performed using the CFX96 qPCR detection system (Bio-Rad, France), and carried out with 5 l of DNA extract and specific primers and a probe targeting a fragment of the C. burnetii 16S DNA gene, as previously described (22), and IS1111 (23,24). Negative controls consisted of DNA extracted from the organs and blood of PBS-challenged mice.…”
Section: Methodsmentioning
confidence: 99%
“…38 This study showed that age and sex of patients did not significantly differ between the two areas. Patients from Cayenne had a significantly higher prevalence of fever (97%) and pneumonia (83%) than did patients from metropolitan France (81% and 8%, respectively).…”
Section: Clinical Featuresmentioning
confidence: 72%
“…This study also showed that the serologic profile of Q fever patients from Cayenne was unusual; significantly higher phase I IgG titers were observed. 38 The main clinical presentation of Q fever in French Guiana is pneumonia, and it has an exceptionally high prevalence. Patients with pneumonia have a good outcome despite a more severe initial clinical presentation.…”
Section: Clinical Featuresmentioning
confidence: 99%